Novel MHC-Independent αβTCRs Specific for CD48, CD102, and CD155 Self-Proteins and Their Selection in the Thymus - Van Laethem, François; Saba, Ingrid; Lu, Jinghua; Bhattacharya, Abhisek; Tai, Xuguang; Guinter, Terry I.; Engelhardt, Britta; Alag, Amala; Rojano, Mirelle; Ashe, Jennifer M.; Hanada, Ken-ichi; Yang, James C.; et al. (Frontiers in Immunology, 2020)
MHC-independent TCRs (TCRs) recognize conformational epitopes on native self-proteins and arise in mice lacking both MHC and CD4/CD8 coreceptor proteins. Although naturally generated in the thymus, these TCRs resemble re-engineered therapeutic chimeric antigen receptor (CAR) T cells in their specificity for MHC-independent ligands. Here we identify naturally arising MHC-independent TCRs reactive to three native self-proteins (CD48, CD102, and CD155) involved in cell adhesion. We report that naturally arising MHC-independent TCRs require high affinity TCR-ligand engagements in the thymus to signal positive selection and that high affinity positive selection generates a peripheral TCR repertoire with limited diversity and increased self-reactivity. We conclude that the affinity of TCR-ligand engagements required to signal positive selection in the thymus inversely determines the diversity and self-tolerance of the mature TCR repertoire that is selected.